2005
DOI: 10.1007/s10535-005-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation in some representatives of the genus Tripleurospermum

Abstract: Genome size has been estimated by flow cytometry in 14 populations belonging to eight taxa (seven species, one of them with two varieties) of the genus Tripleurospermum. 2C nuclear DNA amounts range from 4.87 to 9.22 pg, and nuclear DNA amounts per basic chromosome set from 1.99 to 2.75 pg. Statistically significant differences depending on ploidy level, life cycle or environmental factors such as altitude have been found. Also, genome size is positively correlated with total karyotype length. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
5
14
0
Order By: Relevance
“…The present count agrees with the previous ones carried on this Turkish endemic species in north‐east Anatolian populations (Inceer & Beyazoglu, 2004; Garcia et al ., 2005).…”
Section: Resultssupporting
confidence: 93%
“…The present count agrees with the previous ones carried on this Turkish endemic species in north‐east Anatolian populations (Inceer & Beyazoglu, 2004; Garcia et al ., 2005).…”
Section: Resultssupporting
confidence: 93%
“…Our chromosome count confirms the existence of the tetraploid cytotype of this species, reported by Inceer and Beyazoglu (2004), Garcia et al (2005) and Inceer and Hayirlioglu-Ayaz (2007) on Turkish materials. Apart from this, one count on Armenian plants has reported the diploid level, 2 n = 18 (Avetisian and Oganesian 1995).…”
Section: Resultssupporting
confidence: 90%
“…Most cytological studies conducted in the genera have concentrated on the chromosome count, with little work having been focussed on detailed karyological criteria for taxonomic purposes (Mitsuoka and Ehrendorfer 1972; Inceer and Beyazoglu 2004; Garcia et al 2005). In spite of the very large number of chromosome counts performed in Matricaria , to our knowledge, no chromosomal data on Turkish populations have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The shortest total haploid chromosome length (20 μm) was observed in the Tehran population of T. parthenium. The karyotype length is positively correlated with genome size (Garnatje et al 2004;Garcia et al 2005), so it could be concluded that T. polycephalum subsp. duderanum and T. parthenium (Tehran population) would possess highest and lowest genome size among the studied taxa, respectively.…”
Section: Discussionmentioning
confidence: 99%